Activity-Dependent Arc Expression and Homeostatic Synaptic Plasticity Are Altered in Neurons from a Mouse Model of Angelman Syndrome - Pastuzyn, Elissa D.; Shepherd, Jason D. (Frontiers in Molecular Neuroscience, 2017)
Angelman syndrome (AS) is a neurodevelopmental disorder that results from deletions or mutations in chromosome 15, which usually includes the UBE3A gene. Ube3A protein is an E3 ubiquitin ligase that ubiquitinates proteins and targets them for degradation. The immediate-early gene Arc, a master regulator of synaptic plasticity, was identified as a putative substrate of Ube3A, but there have been conflicting reports on whether Arc is a bona fide E3 ligase substrate. Using multiple approaches, we found no evidence for a physical interaction between Arc and Ube3A in vivo. Nonetheless, activity-induced subcellular distribution of Arc is altered in brains from Ube3am−/p+ mice, with abnormal concentration of Arc at synapses. Furthermore, although activation of Arc transcription is normal, the stability of Arc protein is enhanced in dendrites of hippocampal neurons cultured from Ube3am−/p+ mice. Finally, homeostatic synaptic scaling of surface AMPA receptors does not occur in Ube3am−/p+ hippocampal neurons, reminiscent of neurons that lack Arc protein. Although Ube3A does not seem to bind Arc in a canonical E3 ligase-substrate interaction, Arc-dependent synaptic plasticity is still altered in Ube3am−/p+ mice, which may underlie the cognitive deficits observed in AS.